Isolek Bahasa Simalungun di Kecamatan Gunung Malela, Bandar, Bosar Maligas, Ujung Padang, Tanah Jawa, Kabupaten Simalungun - Nurjana Sihombing; Dwi Widayati (Jurnal Ilmiah Wahana Pendidikan, 2023)
This article aims to analyze the phonological and lexical variations of the Simalungun language in 5 sub-districts in Simalungun Regency. This research is a qualitative descriptive research. This research will be analyzed using the theory of structural dialectology. The data for this study came from speakers of Simalungun in 5 sub-districts in Simalungun Regency, which came from 200 Swadesh vocabularies. The data collection method used was the proficient method with fishing techniques as the basic technique and the all-round proficient technique as an advanced technique. The analytical method used is the matching method with the technique of sorting out the determinants as a basic technique and the comparative comparison technique equates and compares differentiates as an advanced technique. From this study it was concluded that the Simalungun language in the 5 sub-districts in Simalungun Regency has phonological variations, namely vocal variations [e] ~ [i]/#V-. Vocal variations [Ø] ~ [a]/#-. Vocal variations [i] ~ [u]/#K-. Vocal variation [ɛ] ~ [o]/#K-. Vocal variations [a] ~ [i]/#K-. Vocal Variations [U] ~ [ɔ]/-K#. Variation of diphthongs [ɛy] ~ vocal [ɛ]/-#. Vocal variation [ɛ] ~ diphthong [uy]/-#. Vocal variation [ɛ] ~ diphthong [ɛy]/-#. Variation of vocals [o] ~ diphthongs [ow]/-#. Consonant variations [Ø] ~ [h]/#-. Consonant variations [s] ~ [Ø]/#-. Consonant variations [Ø] ~ [d]/#-. Consonant variations [n] ~ [t]/#V- . Consonant variations [Ø] ~ [m]/-V#. Consonant variations [h] ~ [k]/#V-. Consonant variations [m] ~ [b]/#V-. Consonant variations [r] ~ [l]/#V-, as well as sound variations are symptoms of metathesis. There are 56 lexical variations of the Simalungun language from the 200 Swadesh vocabularies studied.